2012
DOI: 10.1523/jneurosci.1782-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Red Nucleus Neurons Actively Contribute to the Acquisition of Classically Conditioned Eyelid Responses in Rabbits

Abstract: The red nucleus (RN) is a midbrain premotor center that has been suggested as being involved in the acquisition and/or performance of classically conditioned nictitating membrane/eyelid responses. We recorded in rabbits the activity of RN and pararubral neurons during classical eyeblink conditioning using a delay paradigm. Neurons were identified by their antidromic activation from contralateral facial and accessory abducens nuclei and by their synaptic activation from the ipsilateral motor cortex (MC) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 65 publications
6
28
0
Order By: Relevance
“…Specific regions in the C3 zone have been identified as the link in the conditioned eyeblink response (Jirenhed et al, 2007 ). Similar to the motor effects observed by Horn et al ( 2010 ) eyeblink resposes of the C3 zone are relayed by the anterior interposed nucleus and the contralateral red nucleus (Morcuendo et al, 2002 ; Pacheco-Calderón et al, 2012 ). In the rat the relay is a separate population of neurons in the dorsolateral red nucleus and the adjoining pararubral area with projections to the facial motor nucleus (Ruigrok and Cella, 1995 ).…”
Section: Is Each Purkinje Cell Zone a Basic Functional Unit?supporting
confidence: 64%
“…Specific regions in the C3 zone have been identified as the link in the conditioned eyeblink response (Jirenhed et al, 2007 ). Similar to the motor effects observed by Horn et al ( 2010 ) eyeblink resposes of the C3 zone are relayed by the anterior interposed nucleus and the contralateral red nucleus (Morcuendo et al, 2002 ; Pacheco-Calderón et al, 2012 ). In the rat the relay is a separate population of neurons in the dorsolateral red nucleus and the adjoining pararubral area with projections to the facial motor nucleus (Ruigrok and Cella, 1995 ).…”
Section: Is Each Purkinje Cell Zone a Basic Functional Unit?supporting
confidence: 64%
“…Notably, recording studies have shown that during eyeblink conditioning, pauses in Purkinje cells responses promote bursts of activity in deep cerebellar nuclear neurons (Fig. 2), which drive the conditioned eyeblink response via the red nucleus [4044]. These pauses (for Purkinje cells) and bursts (cerebellar nuclear neurons) are modified via conditioning to generate the temporal structure of the eyeblink response [45], while convergent motor inputs to downstream brainstem circuitry regulates other movement parameters [44].…”
Section: How Are Timing Signals Emanating From the Cerebellum Decoded?mentioning
confidence: 99%
“…Based on research in animals, it is well established that learning in eyeblink conditioning is a primarily dependent on the cerebellum [4,5]. In addition, several other areas such as the red nucleus [6], thalamus [7], and the somato-sensory cortex [8] participate in regulating eyeblink conditioning. Furthermore, as the task difficulty increases, learning becomes more dependent on the modulatory effects of cerebral structures, most notably the hippocampus [9,10] and the prefrontal cortex [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The error bars represent +/− SEM.lyzed using repeated measures analysis of variance (rmANOVA) with Group (sham vs. real) as the between-subjects factor and Block(1)(2)(3)(4)(5)(6)(7)(8) and Trial Type (CS+ vs. CS−) as within-subjects factors.…”
mentioning
confidence: 99%